Kritik Sosial Dalam Lirik Lagu Album Kanvas Putih Karya Sawung Jabo: Kajian Sosiologi Sastra Dan Implementasinya Dalam Pembelajaran Sastra Di SMA - Ferri Saputra, Ardhiyansah (2016)
The purpose of this study is (1) describe the structure of the building in the lyrics album White Canvas Sawung Jabo (2) describes the social criticism in song album White Canvas Sawung Jabo (3) describe the implementation of research findings in the study of literature in high school. Objects that are examined in this study is the social criticism contained in the song lyrics album White Canvas Sawung Jabo. The data in this study are the words in stanzas and lines on a white canvas album song lyrics while the data source is a song album White Canvas. Namely data collection techniques, using the techniques of literature, see and record. Mechanical validity of data used triangulation theory. Data analysis technique used is to use the model dialektika.Hasil this study are (1) a structural analysis on the album's lyrics White Canvas obtained the essence of the poem (song) consisting of theme, tone, feeling, and mandate, while the method of poetry (lyrics) consists of diction, pengimajian, concrete words, figurative language, diversification, and facial procedures poetry. (2) analysis of social criticism in the song lyrics in the album White Canvas namely the problem of crime, problems of development, poverty, social issues and environmental concerns. (3) the results of this study can be implemented as a learning material based on the standard literature in high school competency listen 5. understand the poem (song) delivered directly / indirectly with the basic competencies 5.1 identify the elements form a poem (song) delivered directly atupun through the tape.